2022
DOI: 10.1021/jacsau.2c00268
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Atom Transfer Thermodynamics of Homologous Co(III)- and Mn(III)-Superoxo Complexes: The Effect of the Metal Spin State

Abstract: Systematic investigations on H atom transfer (HAT) thermodynamics of metal O 2 adducts is of fundamental importance for the design of transition metal catalysts for substrate oxidation and/or oxygenation directly using O 2 . Such work should help elucidate underlying electronic-structure features that govern the OO–H bond dissociation free energies (BDFEs) of metal-hydroperoxo species, which can be used to quantitatively appraise the HAT activity of the correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…However, a couple of studies are worth highlighting. A comparison of structurally analogous M III (O 2 · – ) complexes with different metal ions (M = Co, Mn) in the same [N 3 O 2 ] 2– ligand set found that the nature of M, and the concomitant ground spin states and metal–ligand covalencies, correlated with only small changes in the driving force for H-atom abstraction . In contrast, a series of Cr III (O 2 · – ) complexes with a tetraazacyclotetradecane macrocyclic chelate and different exogenous (Cl – ) or tethered (imidazole, pyridine) axial ligands trans to the O 2 · – ligand exhibited markedly different rates of HAT with C–H substrates …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a couple of studies are worth highlighting. A comparison of structurally analogous M III (O 2 · – ) complexes with different metal ions (M = Co, Mn) in the same [N 3 O 2 ] 2– ligand set found that the nature of M, and the concomitant ground spin states and metal–ligand covalencies, correlated with only small changes in the driving force for H-atom abstraction . In contrast, a series of Cr III (O 2 · – ) complexes with a tetraazacyclotetradecane macrocyclic chelate and different exogenous (Cl – ) or tethered (imidazole, pyridine) axial ligands trans to the O 2 · – ligand exhibited markedly different rates of HAT with C–H substrates …”
Section: Discussionmentioning
confidence: 99%
“…) complexes with different metal ions (M = Co, Mn) in the same [N 3 O 2 ] 2− ligand set found that the nature of M, and the concomitant ground spin states and metal−ligand covalencies, correlated with only small changes in the driving force for Hatom abstraction. 34 In contrast, a series of Cr III (O 2…”
Section: •−mentioning
confidence: 99%
See 2 more Smart Citations
“…One of the key gaps in knowledge hindering our understanding of the O-O cleavage step of these catalysts is the scarcity of Mn III -hydroperoxo complexes that have been trapped and spectroscopically characterized. [13][14][15][16][17] Nam and co-workers have reported Mn III -hydroperoxo complexes supported by tetramethylcyclam (TMC) and a ring-contracted derivative. 14,15 These complexes have intense electronic absorption bands in the UV region (∼400-300 nm) and resonance Raman data for [Mn III (OOH)(TMC)] 2+ showed an 16 O/ 18 O-sensitive band at 792 cm −1 .…”
Section: Introductionmentioning
confidence: 99%